Threshold response of Madagascar's littoral forest to sea-level rise - Virah-Sawmy, M; Willis, K; Gillson, L (Blackwell Publishing Ltd., 2009)
Aim: Coastal biodiversity hotspots are globally threatened by sea-level rise. As such it is important to understand how ecosystems resist, respond and adapt to sea-level rise. Using pollen, geochemistry, charcoal and diatom records in conjunction with previously published palaeoclimatic records, we investigated the mechanism, interactions and ecosystem response and resilience of Madagascar's littoral forest to late Holocene sea-level rise. Location: Sediment sequences were collected along the south-east coast of Madagascar in two adjacent habitats in Mandena; the highly diverse littoral forest fragment and species-poor Erica-matrix. Methods: We used a multi-proxy approach to investigate the relative influence of environmental changes on the littoral ecosystem. We reconstructed past vegetation and fire dynamics over the past 6500 years at two sites in the littoral forest using fossil pollen and macrofossil charcoal contained in sedimentary sequences. Alongside these records we reconstructed past marine transgressions from the same sedimentary sequences using geochemical analyses, and a salinity and drought index through the analysis of fossil diatoms. Results: Our findings indicated that it was the synergistic effect of sea-level rise coupled with rainfall deficits that triggered a threshold event with a switch from two types of littoral forest (an open Uapaca forest and a closed littoral forest fragment) to an Erica-Myrica heath/grassland occurring in approximately less than 100 years. Resilience to sea-level rise differed in the two adjacent habitats, suggesting that the littoral forest fragment was more resilient to the impacts of sea-level change and aridity than the open Uapaca woodland. Conclusions: We demonstrated that the littoral ecosystem was influenced by late Holocene sea-level rise and climatic desiccation. While climate change-integrated conservation strategies address the effects of climate change on species distribution and dispersal, our work suggests that more attention should be paid to the impacts of interactive climatic variables that affect ecosystem thresholds.